2001
DOI: 10.1042/0264-6021:3560461
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Zap-70 phosphorylation sites on LAT (linker for activation of T cells) required for recruitment and activation of signalling proteins in T cells

Abstract: T-cell-receptor (TCR)-mediated LAT (linker for activation of T cells) phosphorylation is critical for the membrane recruitment of signalling complexes required for T-cell activation. Although tyrosine phosphorylation of LAT is required for recruitment and activation of signalling proteins, the molecular mechanism associated with this event is unclear. In the present study we reconstituted the LAT signalling pathway by demonstrating that a direct tyrosine phosphorylation of LAT with activated protein-tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 35 publications
4
95
0
1
Order By: Relevance
“…Though a full understanding of how the kinases phosphorylate the individual tyrosines on LAT in vivo remains unresolved, overexpression and in vitro studies have implicated primarily ZAP-70, but also Lck and Itk in LAT phosphorylation (Zhang et al 1998a;Paz et al 2001;Perez-Villar et al 2002;Jiang and Cheng 2007). Even less is known about the phosphatases that dephosphorylate LAT, however CD148 has been implicated (Baker et al 2001).…”
Section: Phosphorylation Of Latmentioning
confidence: 99%
See 2 more Smart Citations
“…Though a full understanding of how the kinases phosphorylate the individual tyrosines on LAT in vivo remains unresolved, overexpression and in vitro studies have implicated primarily ZAP-70, but also Lck and Itk in LAT phosphorylation (Zhang et al 1998a;Paz et al 2001;Perez-Villar et al 2002;Jiang and Cheng 2007). Even less is known about the phosphatases that dephosphorylate LAT, however CD148 has been implicated (Baker et al 2001).…”
Section: Phosphorylation Of Latmentioning
confidence: 99%
“…In T cells, PI3K regulates the recruitment of proteins that facilitate TCR signal transduction such as PLC-g1, Sos1, RasGAP, Itk, Tec, and Vav. Early studies showed that PI3K bound directly to LAT (Fukazawa et al 1995a;Lahesmaa et al 1995;Paz et al 2001); however more recent studies showed binding of p85 to tyrosine-phosphorylated SLP-76 (Shim et al 2004). Inhibition of PI3K in T cells resulted in reduced TCR-induced calcium influx, Rac1 activation, and Erk1/2 phosphorylation.…”
Section: Molecules Recruited To Lat Via Slp-76 Promote T-cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…We next addressed the effect of Nef on the behavior of SLP-76, a signaling adaptor that is recruited into MCs following TCR engagement in a ZAP70-dependent manner (12). J14SLP-76.YFP cells (Jurkat T lymphocytes stably expressing SLP-76 fused to YFP) were used for these analyses as established model of SLP-76 MC formation (43,44).…”
Section: Nef Potently Disrupts the Formation Of Slp-76 MC Following Tmentioning
confidence: 99%
“…LAT facilitates the formation of several multiprotein complexes and acts as nucleation center for T cell signal transduction (11). Upon phosphorylation at Tyr 191 by ZAP70 (12), LAT recruits SLP-76 into MCs via an additional adaptor protein, GADS (13). Together, the LAT-SLP-76 complex nucleates multiple important downstream signaling events such as calcium flux, MAPK activation, integrin activation, and cytoskeletal organization (14).…”
mentioning
confidence: 99%